Monilethrix. Familial case report. Review of the pathogenetic, clinical and therapeutical acquisitions. - Barbareschi, M.; Angius, A.; Bruscagin, C.; Brauner, I.; Menni, S. (European Journal of Pediatric Dermatology, 2018)
Monilethrix is a disorder of the hair shaft. It is jewel-shaped due to a regular sequence of nodes and internodes. We review the pathogenetic, clinical and therapeutical acquisitions regarding this rare, inherited disorder of hair. The pathognomonic ultrastructural findings of Monilethrix which can be observed by scanning (SEM) and transmission electron microscopy (TEM) were carefully treated. A familial case was reported in order to underline the clinical features and the clinical course of the disease. According to recent therapeutical acquisitions, Monilethrix can be successfully treated in slight and moderate cases.